Sexual Orientation Disparities in Mental Health and Substance Use among Black American Young People in the U.S.A.: Effects of Cyber and Bias-Based Victimisation - Mereish, Ethan H. (Cult Health Sex, 2019)
Few studies have explored sexual orientation disparities in mental health and substance use outcomes among racial minorities. This study examined sexual orientation disparities in depression, suicidality, and substance use among Black American young people in the USA, and the mediating role of cyber and bias-based victimisation in accounting for these disparities. Secondary analyses were performed on data from a probability sample of young people (N = 1,129) collected in a school district in the south-eastern USA. Participants reported socio-demographics, depressive symptoms, suicidality, substance use, and experiences of bias-based and cyber victimisation. With some exceptions, Black participants who were lesbian, gay, bisexual, or mostly heterosexual reported higher rates of depression, suicidal ideation, suicide planning, and substance use than Black heterosexual participants. Black lesbian, gay, bisexual, and mostly heterosexual participants reported more cyber and bias-based victimisation than Black heterosexual participants. Sexual orientation disparities in mental health and, to some extent, substance use were partially explained by both forms of victimisation. Further research is needed address the role of bias-based and cyber victimisation in disparities in mental health and substance use among Black sexual minority young people. The present study carries implications for prevention and treatment efforts for racially diverse sexual minorities.